Historical Roots of Political Extremism: The Effects of Nazi Occupation of Italy - Nicola Fontana; Tommaso Nannicini; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2017)
The Italian civil war and the Nazi occupation of Italy occurred at a critical juncture, just before the birth of a new democracy. We study the impact of these traumatic events by exploiting geographic heterogeneity in the duration and intensity of civil war, and the persistence of the battlefront along the “Gothic line” cutting through Northern-Central Italy. We find that the Communist Party gained votes in postwar elections where the Nazi occupation lasted longer, mainly at the expense of centrist parties. This effect persists until the late 1980s and appears to be driven by equally persistent changes in political attitudes.
Keywords: N00; 330